2008
DOI: 10.1002/hep.22507
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary hemochromatosis in the post- HFE era

Abstract: Following the discovery of the HFE gene in 1996 and its linkage to the iron overload disorder hereditary hemochromatosis (HH) there have been profound developments in our understanding of the pathogenesis of the biochemical and clinical manifestations of a number of iron overload disorders. This article provides an update of recent developments and key issues relating to iron homeostasis and inherited disorders of iron overload, with emphasis on HFE-related HH, and is based on the content of the American Assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
83
2
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 86 publications
(90 citation statements)
references
References 140 publications
4
83
2
1
Order By: Relevance
“…Macrophages degrade the erythrocytederived haemoglobin and release the Fe back into the plasma, so it can be re-utilised for erythropoiesis in the bone marrow. Too much Fe is detrimental to health as excess Fe generates free radicals causing oxidative stress and tissue damage primarily in the liver, heart and pancreas [1][2][3]. Providing further evidence as to the detrimental effects of Fe, it has now been shown that reduction of body Fe stores by phlebotomy therapy, even within the normal physiological range, is associated with reduced mortality from endpoints such as cancer [4].…”
Section: Regulation Of Iron Metabolism In Health and Diseasementioning
confidence: 99%
See 4 more Smart Citations
“…Macrophages degrade the erythrocytederived haemoglobin and release the Fe back into the plasma, so it can be re-utilised for erythropoiesis in the bone marrow. Too much Fe is detrimental to health as excess Fe generates free radicals causing oxidative stress and tissue damage primarily in the liver, heart and pancreas [1][2][3]. Providing further evidence as to the detrimental effects of Fe, it has now been shown that reduction of body Fe stores by phlebotomy therapy, even within the normal physiological range, is associated with reduced mortality from endpoints such as cancer [4].…”
Section: Regulation Of Iron Metabolism In Health and Diseasementioning
confidence: 99%
“…Fe dependent regulation of hepcidin is controlled by bone morphogenetic protein /haemojuvelin/SMAD and HFE/transferrin receptor 2 (TFR2) signalling pathways. The pro-inflammatory cytokine interleukin-6 (IL-6) upregulates liver hepcidin via a STAT3 signalling pathway [1,2]. During anaemia increased erythropoietic activity is required to downregulate hepcidin expression and this is regulated by a number of factors including growth differentiation factor 15, while hypoxia and erythropoietin can also directly impair hepcidin expression.…”
Section: Regulation Of Iron Metabolism In Health and Diseasementioning
confidence: 99%
See 3 more Smart Citations